LEGAL ASSISTANCE IS NOT JUST PRO BONO PUBLICO WORK BUT IT IS A RESPONSIBILITY OF AN ADVOCATE - Utari, Bq. Ishariaty Wika (Jurnal IUS, 2014)
Legal assistance free of charge is the right for the poor to get a plea of an advocate or public defender who works for a legal assistance organization. The principle of equality before the law is guaranteed in the Indonesian legal system for recognition of individual rights. If there is no equality before the law, individual rights was actually absolutely nothing. There is no exception for the equality before the law such as occupation, position, background, origin, immunity, socio-economic strata, rich-poor, race, ethnicity, color, ancestry, culture and others. Legal obligation is the responsibility of an advocate to provide legal assistance free of charge, especially belonging to the client who can not afford the lawyer fees. In countries where the law has been advanced democracies, legal assistance free of charge to the poor is no longer the mercy of the lawyers, but has become a society where the rights of the lawyers are . It has been a consequence of the existence to advocate in the midst of the poor, but have started to realize their rights.Key word: legal assistance for the poor